VISUALIZATION OF COMMUNICATION ANXIETY ON MEDIA COMMUNICATION MUSIC VIDEO "TUTUR BATIN" (International Conference on Social and Islamic Studies, 2022)
Communication anxiety is each individual's reaction to threatening situations, causing psychological pressure. Data from the World Health Organization (WHO) shows that from 2015, around 264 million people have suffered from anxiety disorders. Data from the Ministry of Health throughout 2020 showed that the number of anxiety disorders experienced by the community increased by 6.8%, and as many as 18,373 people experienced anxiety disorders. Anxiety disorders experienced by a person can occur due to external and internal stimuli. The impact of communication anxiety experienced by a person is miscommunication and errors in perceiving communication messages. Individuals will experience a sense of self-discomfort and distrust and have problems in social communication. Messages related to communication anxiety are obtained in the face-to-face communication process and visualized in the form of interesting music videos. One of the music videos that are interesting to study is Yura Yunita's with the title "Tutur Batin". This research method uses the semiotic analysis of Roland Barthes. Primary data was obtained from video clips that showed communication anxiety, especially related to the causative factors. This study aims to identify messages of communication anxiety and the factors that cause a person to experience communication anxiety. The theory used is the theory of Communication Apprehension. Based on the results, several factors cause communication anxiety: environmental factors, reinforcement, assessment, ability, and experience. As for the cast, it is dominated by women, and a negative support system causes a person to feel uncomfortable with himself. This research is expected to be a reference for future research focusing on interpersonal communication and communication media studies.